2008
DOI: 10.5507/bp.2008.025
|View full text |Cite
|
Sign up to set email alerts
|

Operating Management of Central Venous Hypertension Complicating Upper Extremity Dialysis Access

Abstract: Aim:To evaluate the importance of surgical bypass between the terminal part of functional arteriovenous shunt (av) for hemodialysis on upper extremity and inner jugular vein in axillosubclavian venous segment obstruction associated with central venous hypertension.Method: Retrospective assessment of surgical bypass between central segments of av fi stula and ipsilateral/contralateral inner jugular vein using ePTFE graft in 17 patients over a 20 year period (1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…However, his fistula remained functional. Bachleda et al reported (23) that the surgical bypass of an obstructed venous segment proximal to a functioning dialysis access site is an acceptable treatment for relieving central venous hypertension symptoms and salvaging functional dialysis access. Infection is most common with central vein catheter accesses, followed by prosthetic arteriovenous grafts (AVG) and is rare with autogenous fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…However, his fistula remained functional. Bachleda et al reported (23) that the surgical bypass of an obstructed venous segment proximal to a functioning dialysis access site is an acceptable treatment for relieving central venous hypertension symptoms and salvaging functional dialysis access. Infection is most common with central vein catheter accesses, followed by prosthetic arteriovenous grafts (AVG) and is rare with autogenous fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…The largest series of patients treated this way, consisted of 12 patients, 8 of whom achieved patency beyond 8 months. 584 Occlusion of the subclavian vein usually requires other treatment strategies such as jugular vein turndown, 585 extra-anatomical bypass from the axillary vein to the internal jugular vein 586 or decompression followed by subclavian interposition graft. 584…”
Section: Central Venous Occlusive Diseasementioning
confidence: 99%
“…• Bypass of an occluded subclavian (with prosthesis) to the ipsilateral internal jugular, contralateral internal jugular, axillo-axillary; 1,6 • Axillo-axillary, brachial-internal jugular, axillaryipsilateral or contralateral internal jugular bypass; bypass of fistula to jugular vein, of fistula to contralateral subclavian; 1,[7][8][9][10] • Bypass to veins of the lower limbs (axillo-iliac, axillo-popliteal, axillo-femoral, axillo-saphenous); 9,11 • Bypass with interposition of the contralateral internal jugular vein 12,13 or transposition of the ipsilateral jugular vein to the occluded segment; 10,14 • Bypass to the right atrial appendage 15,16 and to the innominate vein; 17 • Banding of the access to control fistula flow;…”
Section: Introductionmentioning
confidence: 99%